Analisis Pengaruh Struktur Modal, Growth Opportunity Dan Cash Holding Terhadap Nilai Perusahaan - Hilda Fauziah Wahyuni; Muhammad Muslih (LPPM UNIBI, 2020)
This study aims to analyze the factors that influence the company on firm value. Research measures that the influence of independent variables simultaneously and partially. In this study, the independent variables used are capital structure (DER), growth opportunity (ASSET GROWTH) and cash holding (CASH). Research using a population of companies in the metal sub sector and the like which are listed on the Indonesia Stock Exchange in 2014-2018. The sampling technique used is purposive sampling and obtained 7 companies that have passed the outlier data, the research period was conducted for 5 years, then obtained 35 sample data. Methods of data analysis in this study using panel data regression analysis using software. The results of this study indicate that simultaneously all independent variables have a significant effect on firm value. Meanwhile, partially the capital structure and cash holding have a significant effect on the positive direction of firm value (PBV). Growth Opportunity does not have a significant effect in a positive direction on firm value (PBV).